Anthrone‐spirolactam and quinoline hybrid based sensor for selective fluorescent detection of Fe3+ ions. (6th July 2020) - Darole, Ratanamala S.; Christopher Leslee, Denzil Britto; Mukherjee, Anagh; Gonnade, Rajesh G.; Karuppannan, Sekar; Senthilkumar, Beeran
Abstract : The synthesis of a novel, and highly selective Fe 3+ ion sensor based on anthrone‐spirolactam and its quinoline hybrid ligand is reported. The designed ligand displayed selective detection of Fe 3+ ions with enhanced fluorescence emission. The complexation of Fe 3+ ion led to a red shift of 32 nm from 420 nm to 452 nm, and a several fold increase in intensity with fluorescent green emission. The complexation (detection) of Fe 3+ ions with ligand resulted in chelation enhanced fluorescence and intramolecular charge transfer through the inhibition of C=N isomerization. This hybrid sensor shows high sensitivity and selectivity, spontaneous response, and works on a wide pH range a minimum detection limit of 6.83 × 10 −8 M. Importantly, the sensor works through the fluorescence turn‐on mechanism that overcomes the paramagnetic effect of Fe 3+ ions. The binding mechanism between the ligand and the Fe 3+ ions was established from the Job's plot method, optical studies, Fourier transfor infrared spectroscopy, NMR titration, fluorescence life‐time studies, and density functional theory optimization. The sensor displayed excellent results in the quantification of Fe 3+ ions from real water samples. Furthermore, due to its biocompatibility nature, fluorescent spotting of Fe 3+ ions in live cells revealed its bioimaging applications. Abstract : A novel anthrone‐spirolactam‐quinoline based hybrid is a fluorescence enhanced selective sensor for Fe 3+ through a strong intramolecular charge transfer process. The sensor show a large fold fluorescence enhancement due to quenching of C=N isomerisation on interaction with Fe 3+ ions. The sensor RSD‐1 provided a minimum detection limit of 6.83 × 10 −8 M and application in in‐vitro live cell imaging.